Measuring Organizational Culture from perceived values – proposal of an instrument - Gigliotti, Letícia Moreira; Paro, Pedro Ernesto Pereira; Gerolamo, Mateus Cecilio (Revista Gestão da Produção Operações e Sistemas, 2020)
The purpose of this paper is to present an instrument that aims to measure organizational culture from perceived values. This research was based on the robust method for culture diagnosis, the Competing Values Framework (CVF). Both theoretical and empirical studies were developed to understand the connection between the values perceived in an organizational context and the type of culture it presents. The development of the instrument followed the main four steps: (1) collection of values from literature; (2) classification of the values regarding the types of culture of the CVF they fit through panel with experts; (3) two applications of this instrument were carried out as well as the application of the Organizational Culture Assessment Instrument (OCAI) – also based on CVF; and (4) proposition of the final (current) version of the instrument. The proposed instrument is a qualitative method, and it is based on respondents’ insights to assess the actual values of the organization. Thus, the results can be considered an approximation of the actual characteristics presented in this environment. By applying this instrument, we expect that a diagnosis of organizational culture can be more straightforward and less error-prone, compared to other instruments that have the same purpose.